Perceived stress in nursing undergraduate students - Ana Luiza Yosetake (SMAD, Revista Electrónica en Salud Mental, Alcohol y Drogas, 2018)
This study aimed to assess the perceived stress levels in undergraduate students from an university of the State of São Paulo, Brazil. Instruments were used for socio-demographic assessment and identification of stressors in the academic space and Perceived Stress Scale, for the measurement of perceived stress. After the data analysis, the overload described by the participants, as well as stressors related to the course and difficulties in managing stress were found as the main results. Thus, it is concluded that the routine of the student, plus the lack of spare time and support networks, may have influence on the mental health and the stress perception of the subjects.